The effect of vide learning media on fourth-grade students’ mathematical learning achievement on fractions - Yusriza, Afifa; Kowiyah, Kowiyah (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2023)
This study examines the effect of video learning media on fourth- grade students’ mathematics learning achievement on fractions. The study aimed to determine if video learning media could enhance students’ understanding and improve their mathematical performance in comparison to traditional teaching methods. The subject of this study is 62 fourth-grade students from a public elementary school in Jakarta. The students were divided into 2 classes which an experimental class and control class. This study used quasi experimental design with quantitative method and non-probability sampling. The results indicated a positive influence of video learning media on fourth grade students’ achievement on fractions, with tcount(8.034) ≥ ttable(2.0003). This study implies that the video learning media is an effective teaching tool in mathematics education.